2014
DOI: 10.4103/0972-124x.134566
|View full text |Cite
|
Sign up to set email alerts
|

Salivary TNF-alpha: A potential marker of periodontal destruction

Abstract: Aims and Objectives:(1) To evaluate the effect of type 2 diabetes mellitus on salivary TNF-α level in chronic periodontitis. (2) To evaluate the effect of smoking on salivary TNF-α level in chronic periodontitis. (3) To compare and correlate TNF-α level with the healthy individuals.Materials and Methods:Subjects aged 30-35 years were included for the study and divided into four groups as a group of 20 systemically and periodontally healthy individuals (group I), a group of 20 subjects with pocket probing depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2,763 studies were identified from Medline and Scopus, and 1,934 studies remained after removing duplicates. Of these, 1,878 studies were ineligible for reasons described in Figure , leaving 56 that were eligible for review. Six studies were excluded because of insufficient data after contacting the authors.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 50 studies, 45 objectively assessed OH using an oral examination. Of these 45 studies, 15 analysed OH as categorical data, 31 as continuous data and one as both. Eleven studies provided the association between periodontitis and oral care habits measured according to the frequency of brushing, interdental cleaning and dental visits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High TNF-α serum levels are maintained by inflammatory and infectious processes associated with chronic periodontitis [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, individuals were divided into five groups according to BI, CAL,PPD as being healthy (all the point: BI: À, CAL: À, PDD < 3 mm); gingivitis (less than 30% points: BI: AE,CAL: À, PDD < 3 mm); mild periodontitis (more than 30% points: BI: +, CAL 2 mm, 3 mm PDD 4 mm); moderate periodontitis (more than 30% points: BI: +, 2 mm CAL 4 mm, 4 mm PDD 6 mm); or severe periodontitis (more than 30% points:BI: +, CAL ! 5 mm, PDD > 6 mm) (Front, Laster, Unis, Gavish, & Nagler, 2013, Singh, Gupta, Bey, & Khan, 2014. Unstimulated saliva specimens were collected by salivette tube (Sarstedt AG & Co, Numbrecht, Germany).…”
Section: Patient Enrollment and Saliva Collectionmentioning
confidence: 99%